2006
DOI: 10.1111/j.1365-2753.2006.00637.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical prediction rules for bacteremia and in‐hospital death based on clinical data at the time of blood withdrawal for culture: an evaluation of their development and use

Abstract: The clinical prediction rules are helpful for improved clinical decision making for bacteremia patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…As in previous studies [33-35], in our study older age was associated with significantly increased rates of mortality (OR, 2.812 [95% CI, 1.039-7.611], p = 0.042). Older patients are often nutritionally or immunologically impaired, making them an easy target for infection and its associated complications [36].…”
Section: Discussionsupporting
confidence: 87%
“…As in previous studies [33-35], in our study older age was associated with significantly increased rates of mortality (OR, 2.812 [95% CI, 1.039-7.611], p = 0.042). Older patients are often nutritionally or immunologically impaired, making them an easy target for infection and its associated complications [36].…”
Section: Discussionsupporting
confidence: 87%
“…al . published a hospital based study with a 19.5% prevalence of bacteraemia and predicting bacteraemia with an ROC-AUC of 0.73 [47]. The prevalence of bacteraemia (19.5%) in this study is higher than generally reported for hospital-based studies and may therefore lack generalizability [10], [11].…”
Section: Discussionmentioning
confidence: 66%
“…11,16 Although ordering blood cultures is a routine clinical behavior when there is concern for an infection, a clinician's ability to subjectively predict who has a BSI only improves the likelihood 2-fold. 6 Despite the availability of multiple scoring systems to aid the clinicians, 10,21,22 our study found that over 50% of cultures were ordered in the setting of fever or leukocytosis, potentially demonstrating a triggered response to an event, rather than a decision based on probabilities. This common clinician instinct to "culture if spikes" is an ineffective practice if not coupled with additional clinical information.…”
Section: Discussionmentioning
confidence: 78%